A High Yield Procedure for the Preparation of 2‐Hydroxynitrostyrenes: Synthesis of Imines and Tetracyclic 1, 3‐Benzoxazines. Issue 15 (21st March 2014) - Tena Pérez, Víctor; Fuentes de Arriba, Ángel L.; Monleón, Laura M.; Simón, Luis; Rubio, Omayra H.; Sanz, Francisca; Morán, Joaquín R.
Abstract: Attempts to synthesize 2‐hydroxynitrostyrenes by a Knoevenagel condensation of salicylaldehyde and subsequent elimination were unsuccessful because of the formation of a stable imine. This could be easily prevented by using secondary amines to catalyze the reaction, which then afforded 2‐hydroxynitrostyrenes in high yields. In addition, the stable imine that was formed by employing ammonium acetate underwent a reaction with phosgene to allow the preparation of benzoxazines in good yields. Abstract : The reaction of salicylaldehyde, nitromethane, and ammonium acetate yields a surprisingly stable imine, which hinders the synthesis of 2‐hydroxynitrostyrene. Herein, we present a procedure to overcome this drawback and report the reaction of this stable imine with phosgene to afford benzoxazines in good yields.